Leadership Styles of Small Business Owners: Linking Theory to Application - Howard, Terry L.; Ulferts, Gregory W.; Hannon, John (Journal of Leadership, Accountability and Ethics, 2019)
To understand small business owners' management and leadership styles, an analytical examination of the different elements of the organization is useful. Although each owner manages a company differently, some fundamental principles are more successful, and yield higher opportunities for achievement, growth, and enhanced productivity over the long term. Business planning is vital. One essential step in planning is to develop a vision for the organization that conveys meaning. Effective management and leadership styles that promote an optimistic vision shared with all members of the organization, especially customers and the general community, yield a higher point of accomplishment for business owners.